Public Policy and Endogenous Beliefs: The Case of Genetically Modified Food - Jayson L. Lusk; Anne Rozan (Journal of Agricultural and Resource Economics, 2008)
When individuals have limited information and are uncertain about the quality of a good, government policy, or the lack thereof, can serve as a signal to consumers about the likelihood of realizing alternatives states of nature. In this paper, we focus on a controversial beliefs about government intervention: The market for genetically modified food. Data from a mail survey were used to estimate an econometric model where beliefs about labeling policy, beliefs about the safety of genetically modified food, and willingness to consume genetically modified food are endogenously determined. Results indicate that consumers who believe the government has a mandatory labeling policy for genetically modified food are more likely to believe genetically modified food is unsafe than consumers who believe no such policy is in place.